The Persistence of the Temporary: The Refugee as an Entrapped Subject - Nastoulis, Angelos (HAPSc Policy Briefs Series, 2020)
This article presents aspects of the refugee crisis with an emphasis on the subject. Turning the attention to the refugee as a person, aspects of their lived experience emerge that cannot be seen with the naked eye. We examine the “identity” of the refugee, the accommodation centers, the politicization of the issue and the attempts to solve the problem. The experience of refugees highlights the problematic policy pursued at European level to resolve the refugee crisis, which affects their integration into local communities.